Clinical routine acquisition protocol for 3D relaxation‐compensated APT and rNOE CEST‐MRI of the human brain at 3T. Issue 1 (14th February 2021) - Goerke, Steffen; Breitling, Johannes; Korzowski, Andreas; Paech, Daniel; Zaiss, Moritz; Schlemmer, Heinz‐Peter; Ladd, Mark E.; Bachert, Peter
Abstract : Purpose: The value of relaxation‐compensated amide proton transfer (APT) and relayed nuclear Overhauser effect (rNOE) chemical exchange saturation transfer (CEST)‐MRI has already been demonstrated in various neuro‐oncological clinical applications. Recently, we translated the approach from 7T to a clinically relevant magnetic field strength of 3T. However, the overall acquisition time was still too long for a broad application in the clinical setting. The aim of this study was to establish a shorter acquisition protocol whilst maintaining the contrast behavior and reproducibility. Methods: Ten patients with glioblastoma were examined using the previous state‐of‐the‐art acquisition protocol at 3T. The acquired spectral data were retrospectively reduced to find the minimal amount of required information that allows obtaining the same contrast behavior. To further reduce the acquisition time, also the image readout was accelerated and the pre‐saturation parameters were further optimized. Results: In total, the overall acquisition time could be reduced from 19 min to under 7 min. One key finding was that, when evaluated by the relaxation‐compensated inverse metric, a contrast correction for B1 ‐field inhomogeneities at 3T can also be achieved reliably with CEST data at only one B1 value. In contrast, a 1‐point B1 ‐correction was not sufficient for the common linear difference evaluation. The reproducibility of the new clinical routine acquisition protocol was similar to the previous state‐of‐the‐art protocol with limits of agreement below 20%. Conclusions: The substantial reduction in acquisition time by about 64% now allows the application of 3D relaxation‐compensated APT and rNOE CEST‐MRI for examinations of the human brain at 3T in clinical routine.